A path and velocity planning method for lane changing collision avoidance of intelligent vehicle based on cubic 3-D Bezier curve. (June 2019) - Chen, Long; Qin, Dongfang; Xu, Xing; Cai, Yingfeng; Xie, Ju
Highlights: l A path and velocity planning method of lane changing is conducted based on cubic 3-D Bezier curve. l The entire path is piecewise and combined with two asymmetrical Bezier curves in the XY plane. l The vehicle velocity is added to the path and dividedly designed by Bezier curve in the Z axis. l Two driving conditions are carried out to demonstrate the effectiveness of the proposed method. Abstract: A novel path and velocity planning method for lane changing collision avoidance of intelligent vehicle based on cubic 3-D Bezier curve is proposed in this paper to enhance the flexibility of path and guarantee the conformity to the realistic lane changing maneuver. Owing to the characteristic of 3-D Bezier curve, the velocity information is appended to the path to establish a real-time correspondence between them. In the XY plane, the integrated path is divided into a collision avoidance path and a lane changing path, which is combined with two asymmetrical Bezier curves. And the velocity planning of two paths is implemented by the same curve in the Z axis. The objective functions and dynamic constraints are formulated to solve the optimal problems of the path and velocity planning for satisfying different traffic situations. The simulations are performed in the CarSim-Simulink co-simulation platform and the results show the performance and effectiveness of the proposed approach.